Metformin-Clinical Pharmacology in PCOs - Dumitrescu, R (J Med Life, 2015)
Oligo-anovulation, hyperandrogenism and insulin resistance characterizes polycystic ovary syndrome (PCOs). Metformin is the oldest insulin sensitizer used in the management of type 2 diabetes mellitus. In PCOs, metformin decreases the serum lipids, androgen and insulin; induces ovulation and regular menstrual cycle; increases the pregnancy rate.